PEMBELAJARAN KAIDAH BAHASA INDONESIA DAN KETERAMPILAN BERBAHASA SECARA TERPADU DENGAN PENDEKATAN FOCUS ON FORM PADA SISWA SEKOLAH MENENGAH PERTAMA - Sumarwati Sumarwati; Atikah Anindyarini; Amir Fuady (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2014)
This study aims to: (1) map the students’ needs to enhance their understanding of grammar (2) map the teachers’ needs to overcome students’ low understanding of grammar, and (3) design a grammar teaching model. This was a research and development study. The research subjects were Grade VIII students of twelve junior high schools. Theresults indicate that (1) the majority of students say that it is necessary to have more intensive teaching and learning of Indonesian grammar; (2) they state that it is necessary to learn all the components of grammar more intensively; (3) all teachers do not deliver the knowledge about grammar beyond the competency standard; (4) the main problemsthat teachers experience in teaching grammar through an integration of all language skills are materials preparation, strategy selection, and assessment; and (5) the teaching model to implement “focus on form” includes instructional process, interactive feedback, text comprehension enhancement, task-based instruction, collaborative tasks, and discoursebased approach.